2006
DOI: 10.1186/bf03351934
|View full text |Cite
|
Sign up to set email alerts
|

The Swarm End-to-End mission simulator study: A demonstration of separating the various contributions to Earth’s magnetic field using synthetic data

Abstract: Swarm, a satellite constellation to measure Earth's magnetic field with unpreceded accuracy, has been selected by ESA for launch in 2009. The mission will provide the best ever survey of the geomagnetic field and its temporal evolution, in order to gain new insights into the Earth system by improving our understanding of the Earth's interior and climate. An End-to-End mission performance simulation was carried out during Phase A of the mission, with the aim of analyzing the key system requirements, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 22 publications
0
48
0
2
Order By: Relevance
“…While testing modeling schemes using the End-to-End synthetic data set for the preparation of the Swarm-Mission (Olsen et al, 2006a), it has been revealed that this slowly increasing lithospheric field contribution leaks into the secular variation (SV) model. In order to avoid this aliasing effect, the GRIMM lithospheric field model from SH degree 17 to degree 80 is subtracted from the data in a preprocessing phase.…”
Section: Model Parameterizationmentioning
confidence: 99%
“…While testing modeling schemes using the End-to-End synthetic data set for the preparation of the Swarm-Mission (Olsen et al, 2006a), it has been revealed that this slowly increasing lithospheric field contribution leaks into the secular variation (SV) model. In order to avoid this aliasing effect, the GRIMM lithospheric field model from SH degree 17 to degree 80 is subtracted from the data in a preprocessing phase.…”
Section: Model Parameterizationmentioning
confidence: 99%
“…7, third panel from top). The simulated data contains magnetospheric sources up to spherical harmonic degree 3 and order 1 and induced degrees and orders up to 45 (Olsen et al, 2006). Due to a narrow local-time sampling by the Swarm satellites, especially at the start of the mission when all three satellites are in the same orbit plane, a source characterised by a spherical harmonic term of order 1 fixed in local-time could appear as a spurious signal in the FTMM with a period equal to the local-time repeat period of the satellites.…”
Section: Hour Local Time Selectionmentioning
confidence: 99%
“…Fournier et al: A case for variational geomagnetic data assimilation with the launch of the SWARM mission around 2010 (Olsen et al, 2006b). …”
mentioning
confidence: 99%